West Syndrome in an Infant With Vitamin B12 Deficiency Born to Autoantibodies Positive Mother - Chong, Pin Fee; Matsukura, Masaru; Fukui, Kaoru; Watanabe, Yoriko; Matsumoto, Naomichi; Kira, Ryutaro (Frontiers in Pediatrics, 2019)
Infantile vitamin B12 deficiency, a rare nutritional disorder in developed countries, is characterized by megaloblastic anemia and non-specific symptoms, including failure to thrive, hypotonia, and seizure. Symptoms usually develop at 6 months of age. Exclusively breast-fed infants of vegan-diet mothers are particularly at risk. We report the case of a 7-month-old boy with West syndrome born to a mother with subclinical vitamin B12 deficiency due to autoantibodies. Electroencephalography revealed the characteristic hypsarrhythmia pattern, whereas cranial magnetic resonance imaging revealed cerebral atrophy and hypomyelination. Biochemical analysis revealed elevated urinary methymalonic acid and homocysteine and reduced plasma methionine. Serum vitamin B12 levels were extremely low in both the child and his mother. The mother tested positive for both anti-intrinsic factor and anti-parietal cell antibodies. Low-dose adrenocorticotropic hormone was effective for seizure control. Contrary to previous reports, age-appropriate neurodevelopment was not achieved despite rapid normalization of metabolic profile with vitamin B12 supplementation. Further investigations failed to detect any causative mutations in the genes associated with developmental and epileptic encephalopathy as well as metabolic and other identifiable disorders known to cause West syndrome. To the best of our knowledge, this is the first reported case in which maternal anti-intrinsic factor antibody was considered to be the reason for infantile vitamin B12 deficiency with West syndrome. Differential diagnosis of West syndrome should include vitamin B12 deficiency due to its treatable nature, and early diagnosis is essential to prevent permanent neurological consequences.